2013
DOI: 10.1155/2013/517072
|View full text |Cite
|
Sign up to set email alerts
|

In VitroCytotoxic, Antioxidant, and Antimicrobial Activities ofMesua beccariana(Baill.) Kosterm.,Mesua ferreaLinn., andMesua congestifloraExtracts

Abstract: The in vitro cytotoxicity tests on the extracts of Mesua beccariana, M. ferrea, and M. congestiflora against Raji, SNU-1, HeLa, LS-174T, NCI-H23, SK-MEL-28, Hep-G2, IMR-32, and K562 were achieved using MTT assay. The methanol extracts of Mesua beccariana showed its potency towards the proliferation of B-lymphoma cell (Raji). In addition, only the nonpolar to semipolar extracts (hexane to ethyl acetate) of the three Mesua species indicated cytotoxic effects on the tested panel of human cancer cell lines. Antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Subsequently, using bioactivity guided approach from the SB crude soxhlet extracts, non-polar (n-Hex) extract and its terpenes rich-fraction (F-3) were selected for additional studies. Observations of current study are consistent with other studies where n-Hex extract from root bark of M. ferrea was shown to be more cytotoxic towards a panel of human cancer cell lines compared with other solvent extracts (Teh et al, 2013). Noteworthy, the current study reports for the first time the in vitro cytotoxic activity of M. ferrea stem bark against HCT 116, PC-3, PANC-1, Capan-1, MIA PaCa-2 and MKN-74 cell lines respectively whereas other studies reported the anticancer activities of blossoms, leaves, flowers, seeds and root bark extracts of M. ferrea (Adewale et al, 2012;Mahavorasirikul et al, 2010;Sukanya and Samart, 2012;Teh et al, 2011Teh et al, , 2013.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Subsequently, using bioactivity guided approach from the SB crude soxhlet extracts, non-polar (n-Hex) extract and its terpenes rich-fraction (F-3) were selected for additional studies. Observations of current study are consistent with other studies where n-Hex extract from root bark of M. ferrea was shown to be more cytotoxic towards a panel of human cancer cell lines compared with other solvent extracts (Teh et al, 2013). Noteworthy, the current study reports for the first time the in vitro cytotoxic activity of M. ferrea stem bark against HCT 116, PC-3, PANC-1, Capan-1, MIA PaCa-2 and MKN-74 cell lines respectively whereas other studies reported the anticancer activities of blossoms, leaves, flowers, seeds and root bark extracts of M. ferrea (Adewale et al, 2012;Mahavorasirikul et al, 2010;Sukanya and Samart, 2012;Teh et al, 2011Teh et al, , 2013.…”
Section: Discussionsupporting
confidence: 92%
“…Mesua ferrea (Penaga lilin) is an ornamental plant of family guttiferae which is extensively studied for its anticancer activities in Asian countries including Malaysia. In vitro anticancer activities of M. ferrea against a variety of cancer cell lines i.e., MCF-7, KB, NCI-H187, NCI-H23, Raji, SNU-1, K562, LS-174T, HeLa, SK-MEL-28, IMR-32, Hep-G2, HT-29 and LIM1215 have already been reported (Mahavorasirikul et al, 2010;Teh et al, 2011Teh et al, , 2013Sukanya and Samart, 2012;Asif et al, 2016b). However, to best of our knowledge, there is no detailed study available that reports the molecular mechanisms responsible for the anticancer effects of M. ferrea stem bark extract against HCT 116 (human colorectal carcinoma) cell line.…”
Section: Introductionmentioning
confidence: 99%
“…The total phenolic content of extracts were measured using Folin-Ciocalteu method with some modifications as described by Teh et al 22 . Gallic acid was used as the standard in the experiment.…”
Section: Determination Of Total Phenolic Content Tpcmentioning
confidence: 99%
“…Scavenging activity of extracts were assessed using DPPH free radical assay 22 . Ascorbic acid was used as the standard in the experiment.…”
Section: Dpph Free Radical Scavenging Activitymentioning
confidence: 99%
“…In addition, in vitro anticancer activities of different parts of M. ferrea towards a variety of cancer cell lines i.e., MCF-7, KB, NCI-H187, NCI-H23, Raji, SNU-1, K562, LS-174T, HeLa, SK-MEL-28, IMR-32 and Hep-G2 have also been reported (Keawsaard et al, 2015;Mahavorasirikul et al, 2010;Teh et al, 2011;Teh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%